THE USE OF MAGNESIUM SULFATE IN PEDIATRIC ANESTHESIOLOGY: EVALUATION OF THE EFFECTIVENESS OF COMBINED ANALGESIA (Herald of the National Children's Medical Center, 2025)
Modern pediatric anesthesiology requires effective and safe techniques to minimize pain, reduce the need for opioids, and ensure a comfortable awakening. The use of multimodal analgesia, including magnesium sulfate (MGSO₄), is a promising approach to optimizing pain relief and muscle relaxation in children. MGSO₄ has a number of pharmacological effects that may be particularly useful in pediatric practice, including reducing pain sensitivity, enhancing the action of muscle relaxants, and stabilizing hemodynamics.
Keywords: magnesium sulfate; multimodal analgesia; children; muscle relaxation; anesthesiology